PENGARUH AKUNTABILITAS, INDEPENDENSI, PENGETAHUAN AUDIT, ETIKA, DAN MOTIVASI AUDITOR TERHADAP KUALITAS HASIL AUDIT INTERNAL - Putri, Ria Febrianita; Husaini, Husaini; Ilyas, Fitrawati (JURNAL FAIRNESS, 2020)
This study aims to look at the effect of accountability, independence, knowledge, audit ethics and motivation on the quality of the work of the government's internal auditors. The study uses attribution theory to explain this with behavior and attitudes that shape the internal government supervisor apparatus, where internal auditors will work in accordance with existing rules, trust ethics, independence, increase knowledge, accountability, and try to improve the quality of work that is more well. This research was conducted at the Bengkulu Province Inspectorate to 57 experienced internal auditors. Data was collected by distributing research questionnaires. Data is processed using SPSS program with multiple linear regression. The results showed that accountability, independence, knowledge, and audit ethics had a positive effect on the quality of the work of internal auditors. Increasing accountability, increasing accountability, increasing knowledge, and enhancing good audit ethics, will improve the work of internal auditors in Bengkulu Province Inspectorate. Motivational variables that were also seen in this study were not proven on the quality of the work of internal auditors. The study provides recommendations for increasing the motivation of internal auditors with various efforts to increase motivation that will support a quality audit process.